2019
DOI: 10.2147/ott.s216362
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of DLL3, CTLA-4 and MSTN Expression in Patients with Small Cell Lung Cancer</p>

Abstract: IntroductionImmune-based and antibody-drug conjugate therapies have shown promise in the treatment of patients with small cell lung cancer (SCLC). However, better predictive biomarkers are needed for selection of the appropriate SCLC patients for these advanced therapies and also for evaluation of the efficacy of these treatments.ObjectiveThe aim of this study was to examine the expression of delta-like protein 3 (DLL3), cytotoxic T lymphocyte-associated protein 4 (CTLA-4), and mesothelin (MSTN) in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…In principle, this notion is consistent with the existing literature. Only 9 previous studies have earlier described associations between high MSLN expression and poor prognosis and/or unfavorable tumor phenotype in these tumor types [ 43 , 45 , 46 , 57 , 74 , 96 , 105 , 106 , 107 ], while there were 7 other studies which could not find associations with clinico-pathological parameters [ 5 , 44 , 47 , 58 , 64 , 65 , 92 ]. The concept of MSLN expression not representing a universal parameter of malignancy is also supported by the frequent MSLN expression in various benign tumors, including Brenner tumors of the ovary, as well as Warthin tumors, pleomorphic adenomas, and basal cell adenomas of the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, this notion is consistent with the existing literature. Only 9 previous studies have earlier described associations between high MSLN expression and poor prognosis and/or unfavorable tumor phenotype in these tumor types [ 43 , 45 , 46 , 57 , 74 , 96 , 105 , 106 , 107 ], while there were 7 other studies which could not find associations with clinico-pathological parameters [ 5 , 44 , 47 , 58 , 64 , 65 , 92 ]. The concept of MSLN expression not representing a universal parameter of malignancy is also supported by the frequent MSLN expression in various benign tumors, including Brenner tumors of the ovary, as well as Warthin tumors, pleomorphic adenomas, and basal cell adenomas of the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…56 In GI-NEC, SCLC and SCBC, DLL3 shows a cytoplasmic distribution in tumor cells (reported as Golgi apparatus-localized in a single SCLC study 114 ) but how this influences Notch signaling is unknown. 27,28,112,113,[115][116][117] In LLC cells, DLL3 localizes to the cell nuclei, inhibiting Notch signaling at the transcriptional level. Akt signaling is activated by DLL3, which promotes LLC cell survival and reduces cell apoptosis.…”
Section: Dll3mentioning
confidence: 99%
“…Finally, we were left with 16 eligible studies after screening the full text, among which 6 articles were included in our final analysis ( Fig. 1) [20][21][22][23][24][25]. Ten articles were excluded for the following reasons: seven articles were review researches and commentaries, one article did not report hazard ratios and Kaplan-Meier curves and 2 articles were abstracts and did not report relevant outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…One interpretation of this result was that DLL3 expression varies between different populations. The American study indicated that the high expression of DLL3 was a marker of good prognosis [21], and there was no significant correlation between DLL3 expression and prognosis in several Japan studies [22,25], while the high expression of DLL3 is a marker of poor prognosis in China studies [20,23]. These results showed that the expression of DLL3 might be different in different populations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation